The Urgency of Principal's Academic Supervision on PAUD Learning Management - Nurazila Sari; Erni Munastiwi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The Urgency of Principal's Academic Supervision on PAUD Learning ManagementThe purpose of this study was to see whether the principal of Annur Kids Kindergarten Pekanbaru had carried out academic supervision and what were the results of the academic supervision. This research is a qualitative research with the type of case study research. The strategy used is an interview by asking five "whys" questions. The importance of the principal's academic supervision on PAUD learning management can be seen from a case study conducted at Annur Kids Kindergarten Pekanbaru. Produce a statement that learning management activities can be carried out properly and directed if the principal carries out academic supervision on a regular basis. The principal of Annur Kids Pekanbaru Kindergarten conducts academic supervision twice a month. Conduct daily learning evaluations by monitoring directly after the teaching and learning process is complete. Students who achieve success in aspects of their development are based on the academic supervision of their school principal